Pergeseran Budaya Bersantai Masyarakat Kota Banjarmasin (Komparasi Pasar Lama dan Kota Lama) - Allif Agust Setiawan; Arif Rahman Hakim (Huma: Jurnal Sosiologi, 2023)
There is a change in the leisure culture in the life of the Banjarmasin City people today, for example, the Mawarung culture in today's life has changed to Nongkrong culture filled with young Banjarmasin people. The point of study compares two places that are the same places to leisure in Banjarmasin, namely Pasar Lama and Kota Lama. This study uses cultural theory and leisure class theory. This type of research is included in qualitative research with a comparative study approach. Data collection techniques by means of observation, interviews and documentation. The research took place from November 2022 to January 2023. The results of this study show several different of the two places to leisure from clothing, places, visitors, menus, facilities, to topics of conversation. There are three main elements that make a cultural shift occur in the two places to leisure, namely the different ideas between the two places, visitor activities, and artifacts or characteristics of places to leisure. The conclusion of this study shows that there is a change in the leisure culture of the Banjarmasin City people from three cultures namely ideas, activities and buildings. Ideas of the past at Pasar Lama and ideas of the present at Kota Lama. Visitor activities at the Pasar Lama are purely leisure and visitor activities at the Kota Lama are leisure while showing off their social status. Most Pasar Lama building represents a simple place and most Kota Lama building represents an aesthetic place. The nongkrong culture as conspicuous leisure in the Pasar Lama was replaced by the culture of nongkrong as conspicuous consumption in the Kota Lama.